Implementasi Program Bermain Sambil Belajar Budaya Untuk Siswa Tunagrahita Di SDLBN Kecamatan Balikpapan Selatan Sebagai Alternatif Pengenalan Kearifan Lokal Dan Budaya Indonesia Sejak Usia Dini - Muhammad Kamaluddin; Umi Sholikah; Rizjal Wahyu (Prodi PGSD FIP UNM, 2018)
Tunagrahita are children who need a special treatments with IQ score between 50-70. Abnormalities of tunagrahita children is like spastic, autism, hyperactivity or learning difficulties. Culture introduction in the early age also has huge urgency especially for tunagrahita children. This thing is suppose to introduce the national identity and local culture from in herited long time ago. Base on that, the playing program with cultural learning has applied in SDLBN Balikpapan Selatan with some methods which are included program introduction, program appliment and evaluation. During the program held, tunagrahita students so hyperactive and low comprehension of each children but with the appliment of this program which apply learning by playing, the volunteer is capable to make the students follow this program with more enthusiast and brave to show their capability. In the end of this program (the final simulation) all parents are invited to join the program so there are social interactions has built between parents and their children. This program is able to be one of the activity which can be applied in any other school because the appliment of the learning methods is communicative and fun for tunagrahita students in order to introduce the local culture of Indonesia.